Personal marketing appeals: How personality dimensions influence feelings toward emotional images - Roos, John Magnus (International Journal of Economic Practices and Theories, 2014)
The aim of this study is to explore how the five-factor model of personality (openness, conscientiousness, extraversion, agreeableness and neuroticism) influences emotional responses to visual stimuli. An experimental design was used where 148 students completed a personality test and reported their emotional response to fourteen visual images. The key-findings are (1) high degree of extraversion influences pleasant affect (i.e. happiness), (2) high degree of neuroticism influences unpleasant affect (i.e. fear and disgust), (3) low degree of openness, extraversion and/or neuroticism influences the absence of emotions (i.e. neutral response). Our results demonstrate that consumers´ immediate perceptions of visual images as stimuli at least partly depend on their personality dimensions, which are shaped by nature and nurture.